Japanese Language Learners Anxiety: Barriers or Successful Support - Purwaningrum, Elisabeth Worobroto; Hamamah, Hamamah; Degeng, Putu Dian Danayanti (Jurnal Budaya, 2020)
Anxiety is one of the affective variables that affect the process of learning a foreign language. The study of anxiety in the field of learning Japanese as a foreign language, especially in universities in Indonesia, is still lacking. High level anxiety is considered a factor that impedes students from achieving good performance. This study aims at investigating the level of anxiety, the relationship among students’ anxiety and gender, and the students’ ability based JLPT level. The design of this study is survey research. The sample was taken from undergraduate students of the Japanese Literature Study Program (N=91). The data was collected by using Horwitz’s (1986) Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire with four factors analysis from Aida (1994). The findings revealed that students’ anxiety was on the moderate level. Moreover, there was no significant correlation between gender and student’s anxiety. However, students’ anxiety affected students’ ability related to their JLPT level.